Pioneering Health Innovation in Society 5.0: The Vital Role of Gut Microbiota in Immune Balance - Liyantifa, Barliyana; Afryansyah, Afryansyah; Barliyan, Muh Agus; Rokhayati, Yuli (Proceeding International Conference on Religion, Science and Education, 2025)
Microbiota, particularly gut microbiota, plays a crucial role in maintaining human health and influencing disease pathogenesis. Microbiota consists of a collection of microorganisms living in the human body, with essential functions in metabolic processes, nutrient breakdown, and metabolite production that contribute to homeostasis and immune balance. Microbiota imbalance (dysbiosis) can lead to health disorders such as infections and autoimmune diseases. This article evaluates various related studies to understand how gut microbiota interacts with the immune system and maintains human health using the Systematic Literature Review (SLR) method and Meta-Analysis of journals on gut microbiota published in Sinta 3 and 4 reputable journals from 2022 to 2024. This research emphasizes the importance of microbiota in disease prevention and maintaining immune system balance while providing insights into future research directions in this field. Gut microbiota not only functions within the gastrointestinal tract but also has extra-intestinal impacts, such as on the immune system, metabolism, and neurology. Dysbiosis can lead to health issues like metabolic syndrome, inflammatory bowel disease, and autoimmune disorders. Factors influencing microbiota composition include diet, antibiotic use, and environmental factors. Microbiota also affects the immune system by modulating T cells and cytokine production, which are vital for maintaining immune balance and preventing excessive inflammatory responses. Recent studies highlight the role of microbiota in preventing allergies, supporting immune system development, and influencing conditions such as asthma and food allergies. The use of probiotics and prebiotics, along with other dietary interventions, has been shown to help maintain microbiota balance and support overall body health. This article aims to enhance knowledge about microbiota and its benefits for health, including aspects like digestion, immunity, mental health, and well-being.